2006
DOI: 10.4161/cc.5.4.2467
|View full text |Cite
|
Sign up to set email alerts
|

AKT Pathway is Activated by 1,25-Dihydroxyvitamin D3 and Participates in its Anti-Apoptotic Effect and Cell Cycle Control in Differentiating HL60 Cells

Abstract: Differentiation therapy for cancer is a developing treatment modality that is based on the anti-proliferative effects associated with differentiation of the malignant cells. 1,25-dihydroxyvitamin D 3 (1,25D) and its analogs are currently being evaluated clinically, alone or in combination with other agents, for treatment of several neoplastic diseases, but their usefulness as single agents may be limited by the enhancement of cell survival in some cell types exposed to 1,25D. In this study we evaluated the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 37 publications
4
72
0
1
Order By: Relevance
“…These include the JNK (Wang and Studzinski, 2001b;Ji et al, 2002;Wang et al, 2003) and the AKT (Zhang et al, 2006) pathways, and as described here, the Raf-1/p90RSK pathway. It is important to elucidate the precise detailed steps of this pathway in leukemia cells, as it has potential to be targeted for therapeutic intervention (Milella et al, 2001;Chang et al, 2003;Konopleva et al, 2005), and it is essential to identify the correct targets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include the JNK (Wang and Studzinski, 2001b;Ji et al, 2002;Wang et al, 2003) and the AKT (Zhang et al, 2006) pathways, and as described here, the Raf-1/p90RSK pathway. It is important to elucidate the precise detailed steps of this pathway in leukemia cells, as it has potential to be targeted for therapeutic intervention (Milella et al, 2001;Chang et al, 2003;Konopleva et al, 2005), and it is essential to identify the correct targets.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we and others have shown that in HL60 cells ERK1/2 is activated in the early phase of 1,25D-induced differentiation, and this can be accentuated by serum starving the cells prior to exposure to 1,25D (Marcinkowska et al, 1997;Marcinkowska, 2001;Wang and Studzinski, 2001a). Other studies have implicated JNK (Ji et al, 2002;Wang et al, 2003;Buitrago et al, 2006), p38 (Wang and Studzinski, 2001a,b;Ji et al, 2002) and AKT (Zhang et al, 2006) pathways in the transmission of the 1,25D-generated signals to the transcriptional machinery in the nucleus. However, the Raf-MEK-ERK pathways remains firmly established as a principal all-purpose signaling cascade (Chang et al, 2003), and as such deserve additional attention regarding its role in the induction of differentiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…232 Activation of the PI3K/Akt pathway was also observed during 1,25-dihydroxyvitamin D3-induced monocytic differentiation of HL-60 cells. 233 Inhibition of the Akt pathway with pharmacologic inhibitors enhanced vitamin D3-induced cell cycle arrest, increased the expression of p27 Kip1 and promoted apoptosis in HL-60 cells. 233 Inactivation of PTEN (phosphatase and tensin homologue), a negative regulator of the PI3K/Akt pathway, results in expansion of bone marrow hematopoietic stem cells.…”
Section: Pi3k-akt Pathwaymentioning
confidence: 99%
“…233 Inhibition of the Akt pathway with pharmacologic inhibitors enhanced vitamin D3-induced cell cycle arrest, increased the expression of p27 Kip1 and promoted apoptosis in HL-60 cells. 233 Inactivation of PTEN (phosphatase and tensin homologue), a negative regulator of the PI3K/Akt pathway, results in expansion of bone marrow hematopoietic stem cells. 234 Moreover, mice with a mutant PTEN develop conditions reminiscent of AML or lymphoid leukemia.…”
Section: Pi3k-akt Pathwaymentioning
confidence: 99%